2007
DOI: 10.1002/jbm.a.31023
|View full text |Cite
|
Sign up to set email alerts
|

The initial attachment and subsequent behavior regulation of osteoblasts by dental implant surface modification

Abstract: The aim of this study was to investigate the influence of hydrophobic acid-etched (A) and coarse-blasted large-grit and acid-etched (SLA) surfaces as well as hydrophilic modified acid-etched (modA) and modified coarse-blasted large-grit and acid-etched (modSLA) surfaces on the behavior of MG63 cells grown on these surfaces through determination of cell attachment and cell proliferation, time-lapse microscopy of fluorescence-labeled cells, and determination of gene expression by reverse transcription-polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
4
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 45 publications
(41 reference statements)
5
83
4
3
Order By: Relevance
“…Implementation of Ti implants with moderately rough surface topography resulted in substantially improved tissue integration of the implants 20) , which is presumably associated with their positive effect on the proliferation and differentiation of osteoblasts 3,21,22) . One of the possible strategies for further development of the implant therapy could be enhancing the angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of Ti implants with moderately rough surface topography resulted in substantially improved tissue integration of the implants 20) , which is presumably associated with their positive effect on the proliferation and differentiation of osteoblasts 3,21,22) . One of the possible strategies for further development of the implant therapy could be enhancing the angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that superhydrophilicity was maintained by storage in distilled water immediately after sandblasting and acid etching of titanium (Ti) 5) , and this surface enhanced cell response 6) . In addition, more differentiated phenotypes of cells grown on the superhydrophilic surface were confirmed by the remarkable increase of alkaline phosphatase activity, osteocalcin, and osteoprotegerin production [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…To improve the osteoconductive and osteogenic properties for optimal osteointegration, the surface of titanium implants was constantly modified, mostly trying to increase its hydrophilicity 7) . The microstructure and the nanostructure of the titanium surface influenced the behavior of mesenchymal precursors of osteoblasts, thus affecting cell proliferation and differentiation towards the osteoblastic lineage [8][9][10][11] . Mesenchymal stem cells are capable of self-renewal and, when appropriately induced, of differentiating into many cellular lineages [12][13][14] , undifferentiated and highly clonogenic cells may be isolated from the dental pulp, the periodontal ligament and the dental papilla 15,16) .…”
Section: Introductionmentioning
confidence: 99%